Global/Local: What Does It Mean for Global Health Educators and How Do We Do It? - Virginia Rowthorn (Ubiquity Press, 2016)
Background: There has been dramatic growth in the number of innovative university programs that focus on social justice and teach community-based strategies that are applicable both domestically in North America and internationally. These programs often are referred to as 'global/local'and reflect an effort to link global health and campus community engagement efforts to acknowledge that a common set of transferable skills can be adapted to work with vulnerable populations wherever they may be. However, the concepts underlying global/local education are undertheorized and universities struggle to make the global/local link without a conceptual framework to guide them in this pursuit. Objectives: This study reports on the outcomes of a 2015 national meeting of 120 global health educators convened to discuss the concepts underlying global/local education, to share models of global/local programs, and to draft a preliminary list of critical elements of a meaningful and didactically sound global/local educational program. Methods: A qualitative analysis was conducted of the discussions that took place at the national meeting. The analysis was supported by videorecordings made of full-group discussions. Results were categorized into a preliminary list of global/local program elements. Additionally, a synthesis was developed of critical issues raised at the meeting that warrant future discussion and study. Findings: A preliminary list was developed of 7 program components that global health educators consider essential to categorize a program as global/local and to ensure that such a program includes specific critical elements. Conclusions: Interest is great among global health educators to understand and teach the conceptual link between learning on both the global and community levels. Emphasis on this link has high potential to unite the siloed fields of global health and domestic community public health and the institutions, funding options, and career pathways that flow from them. Future research should focus on implementation of global/local programming and evaluation of student learning and community health outcomes related to such programs.